Effect of typical and atypical antipsychotic drugs on serum C-reactive protein and lipid profile in schizophrenic patients - Faris A Ahmed (University of Mosul, 2012)
Objectives: To assess the effect of quetiapine and fluphenazine on serum high sensitivity C-reactive protein (hs-CRP) and serum lipid profile in schizophrenic patients. Patients and methods: The subjects comprised two groups of twenty seven newly diagnosed schizophrenic patients for each group. The first group was treated orally with quetiapine at a dose 200-500 mg/day. The second group was treated with fluphenazine intramuscularly at a dose 25 mg every 4 weeks. Twenty seven healthy volunteers were also included as a control group. The patient and the control groups were age and sex matched. The patients were diagnosed by a psychiatrist on the basis of semi-structured interview to determine DMS-IV diagnosis. Clinical symptoms were assessed in 14 of the 18 Brief individual Psychiatry Rating Scale (BPRS) items in order to measure the severity of schizophrenia. Fasting blood samples from the patients were taken for analysis before the beginning of quetiapine or fluphenazine treatment and after 8 weeks of the study. Other blood samples were taken from healthy subjects as a control group. Results: Serum hs-CRP was significantly (p  0.01) higher in the schizophrenic patients before treated by quetiapine or fluphenazine (difference = 382.9% and 395.1% of control, respectively) than controls. The measurement of hs-CRP decreased significantly (p  0.01) after quetiapine treatment by 19.1%, while it was increased significantly (p  0.01) after fluphenazine by 12.3% compared with before treatment values. In the schizophrenic patients, serum total cholesterol (TC) and triglycerides (TG) were significantly higher (p  0.01) than controls, while high density lipoprotein cholesterol (HDL-C) was lower than controls. Quetiapine caused significant increase (p  0.01) in serum TC and TG, while serum HDL-C decreased significantly (p  0.01) compared with the results before treatment. Fluphenazine did not cause any significant change in the lipid parameters. Quetiapine treatment significantly increased (p  0.05) body mass index (BMI), whereas fluphenazine did not change BMI compared with before treatment values. Base time and after 8 weeks of quetiapine or fluphenazine treatment showed significant decrease in the score of BPRS by quetiapine and fluphenazine. Conclusion: Quetiapine depressed CRP and caused dyslipidemia. Fluphenazine raised CRP but it had no effect on lipid profile.